Carbon Monoxide Poisoning in Miami-Dade County Following Hurricane Irma in 2017. (17th July 2018) - Falise, Alyssa M; Griffin, Isabel; Fernandez, Danielle; Rodriguez, Xeniamaria; Moore, Emily; Barrera, Anne; Suarez, Juan; Cutie, Lidice; Zhang, Guoyan
Abstract: Objective: The Florida Department of Health in Miami-Dade County (DOH-Miami-Dade) investigated 106 reported carbon monoxide (CO) exposures over a 9-day timeframe after Hurricane Irma. This report evaluates risk factors for CO poisoning and the importance of heightened surveillance following natural disasters. Methods: Data on CO poisoning cases from September 9 to 18, 2017 were extracted from Merlin, the Florida Department of Health Surveillance System. Medical records were obtained and follow-up interviews were conducted to collect data on the confirmed CO poisoning cases. Data were analyzed using SAS v9.4. Results: Ninety-one of the 106 people exposed to CO met the case definition for CO poisoning: 64 confirmed, 7 probable, and 20 suspect cases. Eighty-eight percent of the affected individuals were evaluated in emergency departments and 11.7% received hyperbaric oxygen treatment. The most frequently reported symptoms included headache (53.3%), dizziness (50.7%), and nausea (46.7%). Three patients expired due to their exposure to CO. Conclusions: Post Hurricane Irma, the DOH-Miami-Dade investigated numerous cases for CO exposure. By understanding who is most likely to be impacted by CO and the impact of generators' location on people's health, education efforts can be tailored to the population most at risk and further CO exposures and related mortalities following natural disasters can be reduced. ( Disaster Med Public Health Preparedness . 2019;13:94–96)